2012
DOI: 10.1186/1746-6148-8-207
|View full text |Cite
|
Sign up to set email alerts
|

Erythrocyte Pyruvate Kinase Deficiency mutation identified in multiple breeds of domestic cats

Abstract: BackgroundErythrocyte pyruvate kinase deficiency (PK deficiency) is an inherited hemolytic anemia that has been documented in the Abyssinian and Somali breeds as well as random bred domestic shorthair cats. The disease results from mutations in PKLR, the gene encoding the regulatory glycolytic enzyme pyruvate kinase (PK). Multiple isozymes are produced by tissue-specific differential processing of PKLR mRNA. Perturbation of PK decreases erythrocyte longevity resulting in anemia. Additional signs include: sever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 37 publications
0
21
0
Order By: Relevance
“…First, collaboration with breeders and breeding associations allowed us to collect a sufficient number of samples to apply strict inclusion criteria and have enough residual data to establish RIs as recommended; [2][3][4] second, RIs are needed in these breeds, as three of them are prone to diseases that need veterinary visits and eventual blood testing (amyloidosis for Abyssinian cats, feline infectious peritonitis for Holy Birman cats, hypertrophic cardiopathy for Norwegian Forest cats). 6 Siberian cats have recently become popular; thus, the rate of inbreeding is likely to have increased. Breed-specific haematological RIs have not been investigated in these four breeds.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, collaboration with breeders and breeding associations allowed us to collect a sufficient number of samples to apply strict inclusion criteria and have enough residual data to establish RIs as recommended; [2][3][4] second, RIs are needed in these breeds, as three of them are prone to diseases that need veterinary visits and eventual blood testing (amyloidosis for Abyssinian cats, feline infectious peritonitis for Holy Birman cats, hypertrophic cardiopathy for Norwegian Forest cats). 6 Siberian cats have recently become popular; thus, the rate of inbreeding is likely to have increased. Breed-specific haematological RIs have not been investigated in these four breeds.…”
Section: Discussionmentioning
confidence: 99%
“…These patterns may arise from the adaptation to environmental conditions, to a specific aptitude (ie, racing horses or dogs) or to the ‘additive’ effect of the generation of new breeds from pre-existing breeds. 6…”
Section: Introductionmentioning
confidence: 99%
“…Pyruvate kinase deficiency Abyssinian, 42 Somali, 42 Bengal, 43 Egyptian Mau, 43 LaPerm, 43 Maine Coon, 43 Norwegian Forest Cat, 43 Savannah, 43…”
Section: Porphyriamentioning
confidence: 99%
“…A causative mutation of the feline PKLR gene was detected in 1997 [ 4 ], while five mutations have been described in dogs [ 6 , 15 , 17 ] and approximately 240 DNA variants and/or mutations in humans [ 10 ]. The mutation causing feline PK deficiency is a deletion of the last 13 bases of exon 5 from mRNA due to a splicing defect, which is consequently correlated with a single nucleotide substitution mutation (c.693+304G>A) of intron 5 in genomic DNA [ 4 , 5 , 12 ]. Although expression studies have not yet been done, it seems likely that with varied splicing, the normal and mutant alleles may be expressed in different quantities which could explain the intermittent signs.…”
mentioning
confidence: 99%
“…A few studies have reported that the frequency of mutant allele for PK deficiency in Abyssinian and Somali cats is high in the U.S.A., Europe and Australia [ 1 , 5 , 8 ]. Furthermore, this mutation has been found in many purebred cats other than Abyssinian and Somali cats in the U.S.A. and Europe and even domestic shorthair cats [ 5 ]. However, there has been no information describing the mutant allele frequency of feline PK deficiency in Japan.…”
mentioning
confidence: 99%